The New Concept of Physiological “Riolan’s Arch” and the Reconstruction Mechanism of Pathological Riolan’s Arch After High Ligation of the Inferior Mesenteric Artery by CT Angiography-Based Small Vessel Imaging - Wang, Ying; Shu, Weibin; Ouyang, Aimie; Wang, Lei; Sun, Yuping; Liu, Guoqin (Frontiers in Physiology, 2021)
Background. Due to the complexity of anatomical relationship between middle colic artery (MCA) and left colic artery (LCA), there is no unified anatomical concept of Riolan’s arch. There is no consensus as to tie off the inferior mesenteric artery (IMA) at its origin or just below the origin of the left colic artery during radical surgery of sigmoid colon and rectal cancers. The study was to investigate the anatomy of short cut anastomosis branch of MCA and LCA at splenic curvature, and to explore how the shortcut pathway was formed as the compensation of anastomosis branches between MCA and LCA under pathological conditions and the reconstruction; and the mechanism of blood flow pathway after high ligation of the inferior mesenteric artery. Methods. Between January 2018 and May 2020, patients with colorectal cancer underwent CTA before surgery were enrolled in the study. The anatomy of short cut anastomosis branch of MCA and LCA was investigated by volume rendering technique (VR) and maximum intensity projection (MIP). GE's small vessel extraction technology (selected VR) was used to directly display these shortcut anastomosis branches on a map, and to establish their three-dimensional anatomical classification. Then, we used the axonometric drawing to make the model more exact. Results: We report the classification of the ascending branch of LCA and the left branch of MCA, display these shortcut anastomosis branches, and establish their three-dimensional anatomical classification. We found that Riolan’s arch is a shortcut pathway for the compensation of anastomosis branches between MCA and LCA under pathological conditions, and that the formation mechanism of shortcut path accords with the principle of hydrodynamics. Conclusions. Our results provide anatomical basis for the battle between high and low ligation of IMA in colorectal cancer surgery, and the new mechanism of pathological Riolan’s arch formation.